El papel del Contador Público en las PYME ante la contabilidad electrónica en Bogotá - Rodriguez Rivera, Marilyn (Universidad Antonio Nariño, 2022)
This degree work is aimed at carrying out a basic study of the current role of public accountants in small and medium-sized companies in Bogotá DC, through which it is sought to find what implications technological advances in systems have for the profession. current electronic accounting. The aim of this study is to identify weaknesses and strengths that allow for possible strategies to be implemented in the training of future accountants at the Antonio Nariño University in Bogotá, in order to carry out this work it was necessary to investigate the antecedents of the accountants' function as Over time, formulating a research question on which the project was based, finding the most appropriate type of methodology for its development, it was also necessary to design a data collection instrument. With the results of this, it seeks to provide suggestions to the Antonio Nariño University Bogota campus, for the training of Public Accountants capable of facing current needs of SMEs in Bogotá, advances in electronic accounting systems and technology in general.